Pengaruh Pembelajaran Course Review Horay Berbantu Media Puzzle Huruf Terhadap Penguasaan Kosakata Siswa Pada Pembelajaran Bahasa Indonesia - Yohana, Nur Elia Putra; Purnanto, Arif Wiyat; Triana, Putri Meinita (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
This study aims to determine the effect of Course Review Horay learning with the help ofletter puzzle media on the vocabulary mastery of second grade students at SD NegeriSurodadi 3 Candimulyo.This study uses a pre-experimental design method type one group pretest-posttest design(single group initial test-posttest). The subjects in this study were saturated samples ortotal samples, namely by involving data collection carried out using the pretest posttestresult assessment technique. The validation test of the pretest posttest results assessmentinstrument was carried out using expert validation. The instrument research test uses avalidity test to test the results of the pretest posttest from the out-of-sample test results,while the instrument reliability test uses the Cronbach Alpha formula. Hypothesis testusing wilcoxon test. Data analysis used non-parametric statistical techniques, namely thez-test or z-test with the help of the IBM SPSS Statistics 22 program.The results of the research data using the z-test or the Wilcoxon signed test, whichobtained a Z value of -3.559 and an asymp sig value. (2-tailed) 0.001 is less than 5% (0.05).Based on the results of data analysis, the average pretest value was 52.5, while the posttestscore was 77.5. From the results of the study, it can be concluded that the use of CourseReview Horay learning aided by letter puzzle media has an effect on students' vocabularymastery.